Eyelid Spindle Cell Lipoma: Case Report and Review of Three Patients in Literature - Toshihiko Matsuo; Kiyoshi Yamada; Yasumasa Monobe; Takehiro Tanaka (Clinical Case Reports)
ABSTRACT A 39‐year‐old woman presented a saucer‐shaped mass in the left upper eyelid and underwent the extirpation at local anesthesia. Pathologically, collagen fibers, capillaries, small vessels, and CD34‐positive spindle cells were dispersed among mature adipose tissues, indicative of spindle cell lipoma. Long‐lasting cyst‐like eyelid masses would be usually dermoid cysts, and spindle cell lipoma would be listed as a rare pathological diagnosis in differential diagnoses of cyst‐like lesions in the upper and lower eyelid.